Study of shock waves and related phenomena motivated by astrophysics. (March 2016) - Drake, R P; Keiter, P A; Kuranz, C C; Malamud, G; Manuel, M; Stefano, C A Di; Gamboa, E J; Krauland, C M; MacDonald, M J; Wan, W C; Young, R P; Montgomery, D S; et al.
Abstract: This paper discusses the recent research in High-Energy-Density Physics at our Center. Our work in complex hydrodynamics is now focused on mode coupling in the Richtmyer- Meshkov process and on the supersonic Kelvin-Helmholtz instability. These processes are believed to occur in a wide range of astrophysical circumstances. In radiation hydrodynamics, we are studying radiative reverse shocks relevant to cataclysmic variable stars. Our work on magnetized flows seeks to produce magnetized jets and study their interactions. We build the targets for all these experiments, and simulate them using our CRASH code. We also conduct diagnostic research, focused primarily on imaging x-ray spectroscopy and its applications to scattering and fluorescence.